PERILAKU KESEHATAN IBU HAMIL DI INDONESIA (ANALISIS DATA PUBLIKASI SDKI 2012) - , HERRY BUDHI SUTRISNO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Maternal health behavior closely associated with the causes of infant mortality and maternal mortality itself. Maternal health behavior need to be considered given the maternal mortality rate in Indonesia is still alarming and far from the MDGâs. With the increasing socio-economic conditions are expected to affect maternal behavior in health care during pregnancy until the postpartum period that will reduce the risk of infant mortality as well as himself. Research on the health behavior of pregnant women using secondary data is data publication IDHS 2012. IDHS is nationwide survey that provides detailed data on maternal and child health as well as child and adult mortality. The variables analyzed are presented in tabular form a cross. By using this analysis it will be easy to understand how the distribution of data that will give a general overview of the survey. Qualitative descriptive analysis used in this study to answer the question. According to the social characteristics, the higher the motherâs education level, the greater the proportion of pregnant women who checkups to health workers. Mother who gave birth in the age group 20-34 years are more checkups. Pregnant women who live in urban areas are more checkups compared with pregnant women who reside in rural areas. Maternal health behavior by province shows that pregnant women who were in the area of Java and Bali tend to be much more checkups than other regions. The number of pregnant women who choose to give birth in a health care facility located on the island of Java and Bali region. This is because the availability and distribution of health care facilities in the area of Java and Bali are quite uneven, both in urban and rural areas.